The trend of marriage dissolution in Seremban, Negeri Sembilan, Malaysia / Nornai'mah Mahadi ... [et al.] - Mahadi, Nornai'mah; Ahmad Jeffry, Nurul Huda; Mohd Zaini, Umairah; Mohamed Yusof, Noreha (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Marriage is the legal procedure of bringing together man and woman in a rightful union. The legal way in fulfilling the intimacy between couples also known as marriage in term of Islam (Sanizah et al., 2014). In Islam, marriage or 'nikah' refers as solemn and sacred social contract between the bride and groom once the 'ijab' and 'qabul' is expressed clearly. Hasbullah and Razak (2017) stated that marriage stage is the start of family institution when the married couples begin to have more dedication and duty towards their families. Maintaining the stability and lasting marriage is one of the difficulties for the married couples. Throughout the marriage, the couples surely will face the ups and downs in maintaining the lifelong marriage. The married couples hold the key to control and protect their marriage so that it will not end up in a divorce. One of the social problems that involve the family institution is known as divorce. Divorce is the legal dissolution of a marriage by a court. Divorce is allowable when the relationship can no longer manage to keep going (Sanizah et al., 2014). Before divorce takes place, the couples will be persuaded to go along with the counselling sessions coordinate by the Jabatan Agama Islam. The counselling sessions are held in hope of reuniting the couples. On condition that if the sessions failed, they can proceed with divorce as it has been officially stated in the Islamic Law. In this study, the researchers would like to examine the trends of marriage dissolution in Seremban.